Analisis Kinerja Keuangan Pemerintah - Rafsanjani, Mahdi; Sumiati, Sumiati (Jurnal Management Risiko dan Keuangan, 2024)
As one of the provincial governments in Indonesia, DKI Jakarta provides financial reports on their official website as a form of government’s accountability. We, as a society, can respond by analyzing the financial performance of DKI Jakarta provincial government. Through this research, We can see how to analyze the financial performance of DKI Jakarta provincial government from 2012 to 2022. DKI Jakarta was led by five different governors during that period. It is interesting to see the difference between the financial performance of DKI Jakarta on each governor. Financial performance can be measured using fiscal decentralization ratio, independence ratio, regional financial efficiency ratio, local income (PAD) effectiveness ratio, growth ratio, and harmony ratio. The result of the research showed that Basuki Tjahaja Purnama has recorded his name on top of every ratio tested. Followed by Anies Rasyid Baswedan with four times on the top three of every ratio tested. On the other hand, Anies also recorded his name four times in the worst of every ratio tested.   Abstrak DKI Jakarta sebagai salah satu provinsi di Indonesia tentunya memberikan laporan keuangan yang disebarkan kepada publik sebagai bentuk pertanggungjawaban pemerintah daerahnya. Masyarakat daerah dapat memberikan respon dengan menganalisis kinerja keuangan dari pemerintah daerahnya. Melalui penelitian ini, dapat terlihat gambaran bagaimana cara menganalisis kinerja keuangan pemerintah provinsi DKI Jakarta tahun 2012 hingga 2022. Dalam kurung waktu 11 tahun tersebut, DKI Jakarta dipimpin oleh 5 Gubernur berbeda sehingga menarik untuk melihat kinerja keuangan DKI jakarta. Kinerja keuangan dapat diukur menggunakkan rasio desentralisasi fiskal, rasio kemandirian, rasio efisiensi keuangan daerah, rasio efektivitas PAD, rasio pertumbuhan, serta rasio keserasian. Hasil dari penelitian yang dilakukan adalah Bapak Basuki Tjahaja Purnama berhasil mencatatkan namanya dalam pencapaian tertinggi di setiap rasio keuangan daerah yang diujikan. Disusul oleh Bapak Anies Rasyid Baswedan yang mencatatkan 4 kali namanya dalam pencapaian tertinggi di rasio keuangan daerah. Meskipun di sisi lain, Bapak Anies Baswedan juga mencatatkan 4 kali namanya dalam hal terburuk dari segi rasio keuangan daerah yang diujikan.